Yellowstone - Lubin, Arthur, 1901-1995; Hunter, Henry; Barrett, Judith, 1914-2000; Universal Pictures (Firm); Cinetel Films ([North Hollywood, CA] : Universal Productions, Inc., 1936)
An ex-con is murdered in Yellowstone National Park while a bank robber's son is searching for the loot his father hid there 20 years before. --
Henry Hunter, Judith Barrett, Andy Devine, Alan Hale, Ralph Morgan, Monroe Owsley.
Photographer, Milton Krasner; editor, Maurice E. Wright; musical director, Herman Heller.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Yellowstone National Park -- Drama; Ex-convicts -- Yellowstone National Park; Park rangers -- Yellowstone National Park; Crime films; Detective and mystery films; Feature films; Internet videos; Streaming video